PERAN IDENTITAS AGAMA DALAM KONFLIK DI RAKHINE MYANMAR TAHUN 20122013 - Sandy Nur Ikfal Raharjo (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
In 20122013, a communal conflct took place in Rakhine, Myanmar. Religion identities between Muslim minoritiy and Budhist majority have been made use to raise violence among parties. This paper tries to analyse whether the differences in religion identity played as structural/root factor of the Rakhine conflct. Through literature review, the result of study shows that religion identity issue was intentionally played by securitizing actors to mobilise people and to accelerate conflct, in order to pursue their own real interest of power domination, land ownership and business chance. Besides, this research also identifis several prolonged discriminative policies and low economic levels as the structural factor of the communal conflct. This paper suggests that stakeholders should empower moderate monk in promoting interfaith dialogue, involve imparsial third party as mediator, and remove all discriminative policies as the ways to optimize the ongoing conflct resolution process.Keywords: Myanmar, religion identity, communal conflct.